The Contributing Factors to the Risk of Diabetes Mellitus among Indonesian Urban Workers - Mahmudah, Mahmudah; Izza, Nailul; Indrawati, Lely; Paramita, Astridya; Indriani, Diah (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Diabetes mellitus (DM) is a non-communicable disease (NCD) with a high morbidity rate and is the third leading cause of death in Indonesia. Some risk factors are associated with the risk of DM; yet, little is known about the effect of such factors on the occurrence of DM in an urban worker population.Purpose: This study aimed to examine the impact of some risk factors on the occurrence of DM among workers in urban areas of Indonesia.Methods: The study used secondary health status data obtained from the 2018 Basic Health Research by the Research and Development Agency, Ministry of Health, Republic of Indonesia, using a cross-sectional approach. The participants consisted of 15,745 urban working adults aged 15-64 years, whose blood glucose levels were examined. The correlation between variables was analyzed using a multivariate logistic regression test. Results: This study showed that 14.8% of DM patients had hypertension, and 14.9% were obese. The percentage of women with diabetes increased with age, particularly affecting informal workers more frequently. Hypertension (aOR=1.76; 95%CI: 1.56-1.99), central obesity (aOR=1.75; 95%CI: 1.54-1.98), daily smoking (aOR=0.63; 95%CI: 0.53-0.76), and age (aOR=8.9; 95%CI: 5.3-15.7) were identified as significant factors contributing to the risk of DM. However, education, physical activity, the consumption of fruits and vegetables, and employment had no discernible impact.Conclusion: Hypertension, obesity, daily smoking, and age were associated with an increased risk of DM in urban workers. The study recommends that companies collaborate with Posbindu for NCDs to check blood pressure and blood sugar levels regularly, and to measure the height and weight of workers periodically.